A trajetória de um sonho: ansiedade e enfrentamento da infertilidade por casais - Freitas, Livia Maria Maulaz (2016)
Most couples plan in having children; it can be the reason for great frustration when they deal with the infertility. Although there is no scientific consensus on the definition of infertility, the World Health Organization considers an infertile couple when the pregnancy does not occur after one year of regular unprotected sexual intercourse. Facing to the infertility, couples look for treatments to achieve their desire for getting pregnant, which, sometimes, can be very long, painful, and stressful for the couple. The objective of this research was to study how couples face to the infertility, investigating the differences between couples based on anxiety indicators, coping strategies and perception of stress related to infertility. Thus, a descriptive exploratory design of quantitative and qualitative character with a convenience sample was adopted. The participants were 7 couples diagnosed with female and male infertility, who declared to be in a stable relationship at least two years. Of the total 57% of participants were invited to participate in the research during query in assisted reproduction clinic of the University Hospital Cassiano Antonio Moraes (HUCAM) of the State of Espirito Santo; 43% of the participants were indicated and participated from the online collection. All were seeking treatment for infertility and agreed to participate in the study by signing the Term of informed consent. They answered individually to the following instruments of psychological evaluation. a) STAI, State-Trait Anxiety Inventory, which assesses anxiety indicators in terms of “traits of anxiety” and “state of anxiety”; b) COPE Inventory, which evaluates strategies in facing stressful situations; and c) Fertile Problems Inventory (FPI), that evaluates the couple´s perception of stress related to infertility. In addition, all responded to a Protocol for a psychosocial profile, elaborated for the research, to identify social demographic and psychosocial variables related to coping with infertility. The protocol data were processed in terms of frequency of occurrence of the variables and the psychological evaluation were processed according to the guidance of their own instruments All data were analyzed quantitatively, in descriptive terms for the sociodemographic data and the psychosocial profile of the couples, and in comparative terms for the anxiety, coping and stress data between women and men of each couple. Data were also analyzed in qualitative terms in case studies of couples, linking sociodemographic and psychosocial data with the indicators of anxiety, coping and stress. It was observed that the average age of woman was 31 years old and the average age of men was 33 years old, the average union of couples was 8.9 years. There was wide variation of family income of the couples; two of them had above R$5000 income and was doing private treatments. For most couples, infertility had female causes and the family had understanding. Only one couple had children. Only one member of the couples declared not to have a religion. Moderate anxiety was presented by both men and woman, although the average for woman was higher for both anxiety dimensions (trait and state). About the coping of couple, “Turn to religion” was more prevalent strategy. Also, the coping strategy “positive reinterpretation” showed high frequency for women and men. Regarding the perceived stress related to infertility, while woman had high stress on the factor “Maternity/paternity”, all the factors presented moderate stress for men, except the “Life without children”, which showed low stress. From the case studies, we observed that variables such as age of the couples, having children, religion and time of marriage seemed to be related to the anxiety and stress indicators in the couple´s coping process face to the infertility. We discussed about those differences between couples in terms of studied variables, anxiety, coping and perception of stress, in order to understand how couples face to the infertility problems and the dilemma of not getting pregnant.